The Role of Exosome-Loaded Hydrogels in Improving Intervertebral Disc Degeneration: A Systematic Review and Meta-Analysis of Preclinical Animal Studies - Bowen Wang; Desheng Xie; Jianming Huang; Zheyuan Huang; Weizong Weng; Danlei Huang; Ying Zhang; Xiaolin Chen (Frontiers in Bioscience-Landmark)
Objective: Intervertebral disc degeneration (IDD) is a major cause of chronic lower back pain, with current treatment options offering limited efficacy. Exosome-loaded hydrogels have emerged as a promising therapeutic approach due to their biocompatibility and regenerative potential, making them a focus of research for IDD treatment. This study systematically evaluates and performs a meta-analysis of the effectiveness of exosome-loaded hydrogels in preclinical models of IDD. Methods: A comprehensive literature search was conducted across four major databases (PubMed, Embase, Cochrane, Web of Science), including animal studies that met predefined criteria. Data extraction and quality assessment were independently performed by two authors. Treatment effects were quantified using standardized mean differences (SMD) with 95% confidence intervals (CI). Outcome measures included disc height index (DHI), magnetic resonance imaging (MRI) grade, histological grade, IDD-related immunohistochemical (IHC) markers (e.g., collagen type II (COL2), matrix metalloproteinase 13 (MMP13)), and aging-related markers (e.g., p16Ink4a-positive cells, p21CIP1A-positive cells). Results: Treatment with exosome-loaded hydrogels significantly enhanced DHI scores at 4 (p = 0.002) and 8 weeks (p < 0.0001), and decreased MRI scores at 8 (p < 0.00001) and 12 weeks (p < 0.0001), and histological assessments. Furthermore, the treatment group exhibited increased COL2 expression at 8 (p = 0.0002) and 12 weeks (p = 0.002), decreased MMP13 levels at 8 (p = 0.0001) and 12 weeks (p = 0.0009), and a reduction in aging markers (p16Ink4a, p21CIP1A, all p < 0.05), suggesting that exosome-loaded hydrogels facilitate intervertebral disc repair through the modulation of molecular pathways. Sensitivity analysis confirmed the robustness of the findings. Conclusions: Exosome-loaded hydrogels show potential for improving the structure and function of intervertebral discs in IDD treatment, potentially slowing degeneration by inhibiting matrix degradation and cellular aging. Further investigation is required to elucidate the underlying mechanisms and to assess the safety and efficacy of these hydrogels for clinical application. The PROSPERO Registration: CRD420250649970 (https://www.crd.york.ac.uk/PROSPERO/view/CRD420250649970).